Development of broadly reactive H5N1 vaccine against different Egyptian H5N1 viruses. Issue 23 (28th May 2015) - Ibrahim, Mahmoud; Sultan, Hesham A.; Razik, Alaa G. Abdel; Kang, Kyung-il; Arafa, Abdel Satar; Shehata, Awad A.; Saif, Yehia M.; Lee, Chang-Won
Abstract: The H5N1 highly pathogenic avian influenza (HPAI) virus was isolated for the first time in Egypt in 2006, since then, the virus has become endemic causing a significant threat to the poultry industry and humans. H5N1 HPAI outbreaks continue to occur despite extensive vaccination programs that have been implemented nationwide in different poultry species. Several studies showed that the co-circulating H5N1 viruses in Egypt are genetically and antigenically distant raising a question on the cross protective efficacy of commercial vaccines. In this study, we introduced mutations at the antigenic sites of the hemagglutinin (HA) to broaden reactivity of the Egyptian H5N1 virus. A reverse genetically created variant H5N1 virus (A/chicken/Egypt/1063/2010) with five amino acid mutations (G140R, Y144F, I190L, K192Q, D43N) in the HA gene showed enhanced cross reactivity. This virus showed up to 16 fold increase in reactivity to the classic-lineageH5N1viruses measured by hemagglutination inhibition (HI) assay while maintaining similar level of reactivity with the variant-lineage viruses compared to wild-type virus. In addition, a single amino acid substitution (N165H), which removes potential glycosylation site at the HA globular head of two classic strains (A/chicken/Egypt/527/2012 and A/chicken/Egypt/102d/2010) broadened the reactivity to antisera generated against H5N1 viruses from different clusters. The broadened reactivity of the mutant viruses were also confirmed by testing reactivity of antisera prepared from the mutant viruses against reference viruses from both classic and variant clades. The virus neutralization test using selected antisera and viruses further confirmed the cross HI results. This study highlights that targeted mutation in the HA may be effectively used as a tool to develop broadly reactive influenza vaccines to cope with the continuous antigenic evolution of viruses.